Occurrences of aflatoxins in selected rice production areas in Malaysia - Khalid, Khalisanni; Napiah, Noorhapizah; Ishak, Ruzaina; Siva, Raseetha; Abdullah, Sumaiyah (Malaysian Society of Plant Physiology, 2022)
Mycotoxins contamination in rice often occurs in the field prior to harvest, processing and storage. The possible coexistence of four mycotoxins in rice including aflatoxin B1, B2, G1 and G2 were investigatedin the present study. The samples of rice were collected in 33 rice production areas of Padiberas Nasional Berhad (BERNAS) Rice Factories (KBB) in Malaysia. These toxins were extracted from the samples, purified and finally quantified by high performance liquid chromatography (HPLC) with fluorimetry detection. Contamination of aflatoxin G1 was found to be the most prominent, followed by B2, G2 and B1. The coexistence of aflatoxin G1 in rice was found in the highest percentage. Occurrences of aflatoxin B1, B2, G1 and G2 at 36 rice production areas showed a significant difference between east, north and central Peninsular Malaysia ranging from 0.45 to 5.98 ng/g. The mean values for aflatoxin B1, B2, G1 and G2 were 3.234, 4.697, 6.588 and 0.773 ng/g, respectively. The total aflatoxin levels for Kuching (7.61 ng/g), KBB Sungai Limau (7.33 ng/g) and KBB Paya Keladi (6.59 ng/g) were found to exceed the levels set by the European Commission (EC) as well as by the Malaysia Food Regulation 1985. Moreover, the B1 levels for Kuching (3.56 ng/g) and Sarikei (2.42 ng/g) samples also exceeded the level set for B1 by the European Commission. Nevertheless, the findings showed that the concentrations of aflatoxin in most of the rice production areas in Malaysia are still below the permissible limit under both the EC and Malaysia